Maritl Characteristics of Household in Ecotourism Centres: The Case of Rural Tourism Development in Plateau State, Nigeria (2009)
Inadequate information on marital culture of communities adjoining ecotourism destinations has led to worrisome sexual exploitation and indirect introduction of sex tours in many communities . The study surveyed the marital culture of communities near ecotourism centres in Pleateu state with the view 410 sampled households distributed over ten communities in five functional tourism centres. Respondents indicated thet female household members in Aningo (83.34%), Naraguta (70.0%) and Pandam (62.22%) communities mostly marry when they are between 15 and 18 years old. Many respondents in Naraguta communties (57.50%) expect male household members to marry as early as from 19 to 22 years unlike in Dong, Gwut and Kabon where expected age of marriage from most men ranges between 23 to29 years as influenced by their bcloseness to Jos city. Most males are in constant search for hard working uneducated wives to sustain their farms while females continuously search for better economic condition. This results in high rate of polygamus, divorce and povert. Tests of relationship between marital culture and educational attainment among women using Chi square were all significant (P<0.05). Households from communities bordering pandam wildlife park are likely to be vulnerable to sexual exploitation during tourism boom; unless the educational level of the women is generally improved.